Las técnicas grafoplásticas para el desarrollo de la motricidad fina en los niños de inicial ii, de la escuela fiscal mixta doctor Édison Calle Loaiza de la ciudad de Loja. Periodo lectivo 2017-2018. - Quizhpe Zhingre, Carmen Patricia (2019)
The research work entitled: THE GRAFOPLASTIC TECHNIQUES FOR THE DEVELOPMENT OF FINE MOTORCYCLE IN CHILDREN INITIAL II, EDISON DOCTOR EDISON CALLE LOAIZA SCHOOL OF THE CITY OF LOJA. LEGAL PERIOD 2017-2018, has as its general objective: To promote the development of fine motor skills in children of Initial II of the Mixed Fiscal School Dr. Edison Calle Loaiza; In the literature review, topics related to the two variables, graphoplastric techniques and the development of fine motor skills were discussed, which included subtopics that served as theoretical support in the analysis of the results, in the development of the research they were used the methods: scientific, analytical-synthetic, descriptive and statistical allowing us to fully develop the research, for the obtaining of the information the techniques will be used as: the survey that was applied to two teachers to know the use of the graphoplastic techniques in the development of fine motor skills; The instrument used was the comparison list that was applied to 15 children that together with the 2 teachers make up the total population investigated. From the application of the checklist it is obtained that 27% are in the acquired stage in the skills corresponding to fine motor skills; after applying the proposal, post-test a positive advance in fine motor skills was achieved, resulting in 73% in acquired fine motor skills. Therefore, it is concluded that it is necessary the activities of the graphoplasic techniques since they significantly influence the development of fine motor skills, when applying them frequently the child will improve their coordination and motor development.